Strategi Komunikasi Bisnis OYO Hotels and Homes Indonesia Di Masa Pandemi Covid-19 Melalui Program Sanitized Stays - Gan Gan Giantika (Universitas Bina Sarana Informatika, 2021)
Abstract - The hotel industry is one of the industries that has a major contribution to the Indonesian economy. The COVID-19 pandemic, which has been ongoing since early 2019, has had a negative impact on various industries, including the hotel industry. Indonesia is one of the regions in the world affected by COVID-19. The hotel industry has experienced a very drastic decline in occupancy, therefore it is necessary to implement an appropriate and effective business communication strategy in order to stabilize the declining occupancy. The purpose of this research is to find out how the business communication strategy implemented by OYO Hotels and Homes Indonesia during the Covid-19 Pandemic through the Sanitized Stays Program. The method used in this research is descriptive qualitative method by collecting factual data based on observations, and documentation and literature relevant to this research. The results of the research and the conclusion that OYO Hotels and Homes Indonesia carried out business communication strategy activities through the Sanitized Stays program were in accordance with the objectives of the hotel, namely stabilizing occupancy during the Covid-19 pandemic.Keywords : Strategy, Communication, Business, Sanitized Stays Program